The Role of Melatonin as a Hormone and an Antioxidant in the Control of Fish Reproduction - Maitra, Saumen Kumar; Hasan, Kazi Nurul (Frontiers in Endocrinology, 2016)
Reproduction in most fish is seasonal or periodic and the spawning occurs in an appropriate season to ensure maximum survival of the offspring. The sequence of reproductive events in an annual cycle is largely under the control of a species-specific endogenous timing system, which essentially relies on a well-equipped physiological response mechanism to changing environmental cues. The duration of solar light or photoperiod is one of the most predictable environmental signals used by a large number of animals including fish to coordinate their seasonal breeding. In vertebrates, the pineal gland is the major photo-neuroendocrine part of the brain that rhythmically synthesizes and releases melatonin (N-acetyl-5-methoxytryptamine) into the circulation in synchronization with the environmental light-dark cycle. Past few decades witnessed an enormous progress in understanding the mechanisms by which melatonin regulates seasonal reproduction in fish and in other vertebrates. Most studies emphasized hormonal actions of melatonin through its high-affinity, pertussis toxin-sensitive G-protein (guanine nucleotide binding protein) coupled receptors on the hypothalamus-pituitary-gonad (HPG) axis of fish. However, the discovery that melatonin due to its lipophilic nature can easily cross the plasma membrane of all cells and may act as a potent scavenger of free radicals and stimulant of different antioxidants added a new dimension to the idea explaining mechanisms of melatonin actions in the regulation of ovarian functions. The basic concept on the actions of melatonin as an antioxidant emerged from mammalian studies. Recently, however, some new studies clearly suggested that melatonin, apart from playing the role of a hormone, may also be associated with the reduction in oxidative stress to augment ovarian functions during spawning. This review thus aims to bring together the current knowledge on the role of melatonin as a hormone as well as an antioxidant in the control of fish reproduction and shape the current working hypotheses supported by recent findings obtained in carp or based on knowledge gathered in mammalian and avian species. In essence, this review highlights potential actions of melatonin as a hormone in determining temporal pattern of spawning and as an antioxidant in regulating oocyte maturation at the downstream of HPG axis in fish.